Between Gen X and Y: How Do Generational Differences Affect Science Teachers’ TPACK Abilities? - Iswadi Iswadi; Hendra Yulisman; Samsuar Samsuar; Suryani Suryani (Jurnal Penelitian Pendidikan IPA, 2023)
Between 2020 and 2023, two groups of people have relatively the same experience in using technology, namely Generation X and Generation Y. Teachers from these two generations are expected to have the ability to integrate technology into their learning activities. The framework that can be used to identify these abilities is TPACK. This quantitative survey aims to see the differences in the TPACK abilities of biology teachers based on generations X and Y. The research sample consisted of 68 science teachers from Aceh Province. The data is distributed using Google Forms and analyzed by descriptive and inferential statistics. The results show that there is a significant difference between the TPACK abilities of teachers from generation X and generation Y. Another exciting result is that teachers from generation Y have slightly better TPACK abilities than teachers from generation X. The results of this study suggest that teachers, educational lecturers, and educational students should always try to integrate the latest technology into learning activities.